Static and Kinetic Studies of the Adsorption/Desorption of H and OH Ions on Alumina in Aqueous NaNO Solution - Chu Taiwei; Du Jinzhou; Tao Zuyi (Adsorption Science & Technology, 1997)
The adsorption/desorption of H + and OH − ions under static conditions on to alumina in aqueous NaNO 3 solution was studied at 30°C by potentiometric titration and calculations undertaken using the triple layer model (TLM). Intrinsic dissociation constants and intrinsic complexation constants at 30°C were used to calculate surface charge density, surface potential and surface species as a function of pH and ionic strength (I). Related adsorption/desorption studies of H + and OH − ions under dynamic conditions on to alumina in aqueous NaNO 3 solution were studied by means of the concentration-jump technique. Mechanistic information regarding H + and OH − ion adsorption/desorption on to alumina was discussed using the experimental data in conjunction with the TLM.